2011
DOI: 10.1093/europace/eur318
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias originating from the aortomitral continuity: an uncommon variant of left ventricular outflow tract tachycardia

Abstract: We report a series of ventricular arrhythmias arising from the AMC with different R/S wave transition patterns in the precordial leads on the electrocardiogram. There may be a relationship between ventricular arrhythmias from AMC and AVNRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 23 publications
3
49
0
Order By: Relevance
“…The CASs and left ventricular outflow tract are major regions of interest for interventional cardiologists who perform percutaneous coronary intervention, radiofrequency catheter ablation (Kamakura et al, 1998;Daniels et al, 2006;Kumagai et al, 2008;Lin et al, 2008;Yamada et al, 2008a;Steven et al, 2009;Zhang et al, 2009;Yamada et al, 2010a;Yamada et al, 2010b;Letsas et al, 2011;Chen et al, 2012), and transcatheter aortic valve replacement (Cribier et al, 2002;Binder et al, 2012;Samim et al, 2013). The fluoroscopic definition of the anatomy around the left ventricular outflow tract is quite variable and a 3-D anatomical recognition within the cardiac contour seems difficult because of the morphological complexity of this area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CASs and left ventricular outflow tract are major regions of interest for interventional cardiologists who perform percutaneous coronary intervention, radiofrequency catheter ablation (Kamakura et al, 1998;Daniels et al, 2006;Kumagai et al, 2008;Lin et al, 2008;Yamada et al, 2008a;Steven et al, 2009;Zhang et al, 2009;Yamada et al, 2010a;Yamada et al, 2010b;Letsas et al, 2011;Chen et al, 2012), and transcatheter aortic valve replacement (Cribier et al, 2002;Binder et al, 2012;Samim et al, 2013). The fluoroscopic definition of the anatomy around the left ventricular outflow tract is quite variable and a 3-D anatomical recognition within the cardiac contour seems difficult because of the morphological complexity of this area.…”
Section: Discussionmentioning
confidence: 99%
“…Many electrocardiographic characteristics that predict the origin of an arrhythmia have been reported to occur around this site (Kamakura et al, 1998;Daniels et al, 2006;Kumagai et al, 2008;Lin et al, 2008;Yamada et al, 2008a;Steven et al, 2009;Zhang et al, 2009;Yamada et al, 2010a;Yamada et al, 2010b;Letsas et al, 2011;Chen et al, 2012). Because approaches based on the QRS-wave morphology during an arrhythmia and endocardial or epicardial pacing are inductive, the correct recognition of the fluoroscopic anatomy for defining the exact site of the electrode position should be a fundamental practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although successful ablation of arrhythmias at the AMC has been described, [1][2][3][4][5][6][7][8][9][10][11][12] the exact nature of the arrhythmogenic substrate remains unknown. 4,[13][14][15][16][17] While no myocardium has been found in this region, animal studies have shown that cells with electrophysiological properties similar to that of the atrioventricular (AV) junctional cells are present near the mitral annulus.…”
Section: Possible Arrhythmogenic Substratementioning
confidence: 99%
“…Although successful ablations of arrhythmias at the AMC have been reported in the literature, [1][2][3][4][5][6][7][8][9][10][11][12] knowledge of the clinical, electrocardiographic (ECG), and electrophysiological characteristics of idiopathic ventricular arrhythmias (VAs) arising from this region remains limited. Furthermore, being a fibrous structure, the exact nature of the arrhythmogenic substrate remains unclear.…”
Section: Introductionmentioning
confidence: 99%